Role of a heterotrimeric G‐protein, Gi2, in the corticogenesis: possible involvement in periventricular nodular heterotopia and intellectual disability. Issue 1 (29th November 2016) - Hamada, Nanako; Negishi, Yutaka; Mizuno, Makoto; Miya, Fuyuki; Hattori, Ayako; Okamoto, Nobuhiko; Kato, Mitsuhiro; Tsunoda, Tatsuhiko; Yamasaki, Mami; Kanemura, Yonehiro; Kosaki, Kenjiro; Tabata, Hidenori; et al.
Abstract: We analyzed the role of a heterotrimeric G‐protein, Gi2, in the development of the cerebral cortex. Acute knockdown of the α‐subunit (Gαi2) with in utero electroporation caused delayed radial migration of excitatory neurons during corticogenesis, perhaps because of impaired morphology. The migration phenotype was rescued by an RNAi‐resistant version of Gαi2. On the other hand, silencing of Gαi2 did not affect axon elongation, dendritic arbor formation or neurogenesis at ventricular zone in vivo . When behavior analyses were conducted with acute Gαi2‐knockdown mice, they showed defects in social interaction, novelty recognition and active avoidance learning as well as increased anxiety. Subsequently, using whole‐exome sequencing analysis, we identified a de novo heterozygous missense mutation (c.680C>T; p.Ala227Val) in the GNAI2 gene encoding Gαi2 in an individual with periventricular nodular heterotopia and intellectual disability. Collectively, the phenotypes in the knockdown experiments suggest a role of Gαi2 in the brain development, and impairment of its function might cause defects in neuronal functions which lead to neurodevelopmental disorders. Abstract : We propose the role of a heterotrimeric G‐protein, Gi2, in the brain development. We then identified a de novo heterozygous missense mutation of the α‐subunit, GNAI2, in a patient with periventricular nodular heterotopia and intellectual disability. Although pathophysiological significance of this mutation remains to be clarified, gene abnormalities of GNAI2 might be involved in the pathogenesis of neurodevelopmental disorders.